Nasopalatine duct cyst: a case report within 3 years follow-up - Conte Neto, Nicolau [UNESP] (2010)
The nasopalatine duct cyst (NPDC) is considered to be the most common non-odontogenic cyst in oral cavity. These cysts are usually asymptomatic; however they can result in swelling, pain and drainage. The radiological analysis can reveal a round, oval or heart shaped well-demarcated image, which can be confounding with inflammatory lesions. The aim of this paper is report a clinical case of NPDC in a patient of 33 years old, occurring near a periapical inflammatory lesion. During clinical examination, it was not possible to detect swelling of the anterior palate and patient didn´t complain painful symptoms. Surgical treatment, enucleation, was performed under local anesthesia and there was no post operative complications. Histological results showed the presence of a cuboidal and respiratory epithelium associated with vessels, nerves and inflammatory cells. The patient’s 3 years follow-up was uneventful with subsequent bone regeneration and no sign of the lesion recurrence.